Development of Cookie Products from Sweet Potato - Charoenphun, Narin (Journal of Food Technology, Siam University, 2018)
Sweet potatoes contain many high nutrients, which are high carbohydrate and fiber. Moreover, they are delicious and inexpensive. The objectives of this research were to determine the effect of drying temperature on preparation of white, yellow, orange and purple sweet potato flours and to study the optimal ratio of sweet potato flour partially replaced by wheat flour in cookie products. Furthermore, the development of sweet potato cookie product was investigated. The optimization of sweet potato flour preparation with drying temperature of 50 ºC, 60 ºC and 70 ºC was studied. It was found that appropriated drying temperature for preparation of sweet potato flours was 60ºC for 28 hr. In terms of cookie product, the use of sweet potato flour partially replaced by wheat flour in cookie products was investigated by mixture design experiment for nine formulas. The results showed that the optimal formulation of cookie product contained of 40 g salted butter, 30 g sweet potato flour, 30 g wheat flour, 30 g icing sugar, 15 g eggs, 0.5 g baking powder and 0.2 g vanilla powder. It had the highest overall liking scores (7.77±0.82), which referred criteria as like moderately. In addition, the total antioxidant of sweet potato cookie was investigated by DPPH method. Results was found that total antioxidant of white, yellow, orange and purple sweet potato cookie had 45.20, 75.67, 93.16 and 133.59 mg eq Trolox/100 g, respectively. In conclusion, orange and purple sweet potato cookie had good quality and high nutritional value for consumer. It can be produced for selling on the health-conscious market in the future.